2020
DOI: 10.17294/2330-0698.1794
|View full text |Cite
|
Sign up to set email alerts
|

Cole Relaxation Frequency as a Prognostic Parameter for Breast Cancer

Abstract: We previously reported successful classification of breast cancer versus benign tissue using the Cole relaxation frequency measured on tissue excised during breast surgery as part of a study at two urban hospitals in the U.S. Midwest. Using that health system's cancer registry, we have discovered retrospectively that outcomes for patients who participated in the initial study can be classified correctly in 3 well-differentiated categories: nonrecurrent (NR); recurrent with no metastasis (RNM); and recurrent wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 16 publications
(17 reference statements)
2
5
0
Order By: Relevance
“…The positive correlation between CRF biomarker and pathologically analyzed cancer-induced fibrosis in PC may be similar to that shown in breast cancer [42]. Gregory et al [42] previously reported using the CRF biomarker as a prognostic indicator for the aggressiveness of breast cancer.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…The positive correlation between CRF biomarker and pathologically analyzed cancer-induced fibrosis in PC may be similar to that shown in breast cancer [42]. Gregory et al [42] previously reported using the CRF biomarker as a prognostic indicator for the aggressiveness of breast cancer.…”
Section: Discussionsupporting
confidence: 71%
“…The positive correlation between CRF biomarker and pathologically analyzed cancer-induced fibrosis in PC may be similar to that shown in breast cancer [42]. Gregory et al [42] previously reported using the CRF biomarker as a prognostic indicator for the aggressiveness of breast cancer. In that retrospective study, a strong correlation was found between the CRF values of tumor excisions measured at time of surgery and long term patient outcomes in terms of recurrence or time-cancer-free [42].…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…129 Some researchers have identified a frequency-dependent parameter, the Cole relaxation frequency (CRF), for classifying tissues and distinguishing cancerous tissue from healthy breast tissues. 130 Defined as the frequency where the imaginary component of impedance vs frequency peaks in a Z IM − frequency plane of a Cole−Cole plot the CRF differs for cancerous vs noncancerous tissues. Based on the hypothesis that cancer decreases the polarizability of cells and hence lowers the capacitance of cells, the CRF of normal tissue (0.001−0.1 MHz) shifts to higher frequencies (0.1−2 MHz) for cancerous cells.…”
Section: Bis For Malignancymentioning
confidence: 99%
“…Cancer affects the packing state of tongue cells resulting in widening of extracellular space leading to a more conductive path for ion migration at lower frequencies (reducing impedance compared to healthy parts of the same tongue as well as tongues of healthy patients) . Some researchers have identified a frequency-dependent parameter, the Cole relaxation frequency (CRF), for classifying tissues and distinguishing cancerous tissue from healthy breast tissues . Defined as the frequency where the imaginary component of impedance vs frequency peaks in a Z IM –frequency plane of a Cole–Cole plot the CRF differs for cancerous vs noncancerous tissues.…”
Section: Clinical Applicationsmentioning
confidence: 99%